(untitled) (International Journal of Food and Nutritional Sciences, 2021)
India boasts one of the largest biodiversity regions in Asia, characterized by a wealth of medicinal and aromatic plant diversity. The therapeutic applications of these plants reflect a longstanding tradition across various cultures. The genus Catharanthus has some medicinal properties, herbs known for enormous potentialities and to be employed for the treatment of cancer in some parts of the world paving a way for replacing the allopathic treatments with the natural ones. The dissolvable concentrates of Catharanthus roseus indicated huge antibacterial movement against Bacillus subtilis, Escherichia coli, Pseudomonas, Staphylococcus aureus and so on. Leave and flower concentrate of Catharanthus roseus recorded noteworthy action against all the test microorganisms.